Assessment of light transmission aggregometry on the routine coagulation analyzer Sysmex CS-2500 using CE-marked agonists from Hyphen Biomed. (19th May 2019) - Bret, V.-E.; Pougault, B.; Guy, A.; Castet, S.; Huguenin, Y.; Pillois, X.; James, C.; Fiore, M.
Abstract: Light transmission aggregometry (LTA) is still considered as the "gold standard" for platelet function assessment but, as acompletely manual technology, it is labour intensive. This challenge can be overcome by performing platelet aggregometry in anautomated method on a routine coagulation analyzer. We aimed to compare and correlate results obtained from a traditional manual LTA solution realized in our Reference Center with an optimized automated system using CE-marked agonist reagents. Platelet rich plasma from patients with suspected platelet disorders, von Willebrand disease or antiplatelet therapy have been assessed using a wide range of agonist concentrations. Results were expressed as Maximal Platelet Aggregation and correlation was analyzed using the Passing and Bablok regression test. Platelet aggregometry studies were performed in 49 samples. Maximal aggregation response with ADP (0.5-10 μM), collagen (2 mg/μL), ristocetin (1.2 mg/mL) and arachidonic acid (1 mM) agonists showed significant correlation between the two aggregometers (p< .001). We observed a more variable response using lowconcentrations of ADP (≤5 μM). Moreover, we also noted discrepancies with the low dose of ristocetin, showing excessive paradoxical agglutination with the CS-2500, suggesting that a lower ristocetin dose should be used with this system. These data show that CS-2500 has the advantages of a walk-away technology and the use of CE-marked reagents also permit the possibility of an easier certification.